Redução da emissão de co2 de vigas mistas protendidas de aço e concreto via algoritmos metaheurísticos - Fiorotti, Kamila Madeira (2023)
The use of external prestressing has been increasing in recent decades, mainly in the reinforcement of beams in bridges and viaducts, due to its performance and less interference in the local traffic. ABNT NBR 6118:2014 deals with the application of prestressing in concrete structures, and ABNT NBR 8800:2008 presents the requirements for the design of steel beams as well as composite steel and concrete beams. However, the use of prestressing applied to these types of structures is not addressed by Brazilian technical standards. The present study aims to contribute to filling this gap by formulating the optimization problem of prestressed steel and concrete composite beams with full interaction in pretension and straight cables, to minimize CO2 emissions. The dimensions of the doubly symmetric and monosymmetric profiles, the choice of the steel deck slab, the choice of strength, the dimensions of the concrete slab and the number of prestressing cables were considered as the design variables for the optimization problem. To solve the optimization problem, metaheuristic algorithms, such as the Genetic Algorithm (GA) and the Particle Swarm Algorithm (PSO), were applied to compare the optimized solution. Experimental and numerical problems available in the literature were analyzed in the proposal validation step. A parametric analysis was carried out to identify which geometric patterns most influence the solution, as well as the final emissions. From the analysis, it was concluded that the final emissions are strongly influenced by the shape of the steel of slab and the metallic profileof beam, and that the use of prestressing is more suitable for beams with larger spans. It was also verified that the use of concrete with higher resistance in the slabs is more indicated for beams with larger spans. The final results indicates that the proposed formulation can be used to design more sustainable structures.